Implementasi Strategi Student Team Achievement Divisions Dalam Pembelajaran Tematik Terpadu Di SD Darus Sholah Jember - Nasilah, Nasilah; Winarno, Ahmad (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2021)
This research was conducted at SD Darus Sholah, Jember which aims to answer the main problems related to the implementation of the Student Team Achievement Divisions learning strategy in integrated thematic learning. The problem studied in this research is the Implementation of the Student Team Achievement Divisions Strategy in integrated thematic learning at SD Darus Sholah, Jember. This research approach uses a qualitative approach with the type of phenomenological research. Methods of data collection using interviews, observation and documentation. Data analysis used the interactive model of Miles and Huberman, with the process of data collection, condensation, data display, and data verification. To test the validity of the data using triangulation. The results of this study indicate that: 1) At the presentation stage, the teacher starts with story material, reviews previous material, and learning activities in teams. 2) The teacher prepares a worksheet as a guide for group work and each member can contribute, the teacher makes observations, provides guidance, motivation, and assistance if needed. 3) Individual tests in groups. 4) Score development for individuals, the teacher combines the previous score with the final score. 5) Appreciation for the team is based on the assessment of individuals in the group so that the process of group assessment recapitulation is based on individual assessment of each group. Keywords: STAD Model; Learning, Thematic; Primary school Penelitian ini dilakukan di SD Darus Sholah Jember yang bertujuan untuk menjawab pokok permasalahan berkaitan dengan penerapan strategi belajar Student Team Achievement Divisions dalam pembelajaran tematik terpadu. Permasalahan yang dikaji dalam penelitian ini, Implementasi Strategi Student Team Achievement Divisions dalam pembelajaran tematik terpadu di SD Darus Sholah Jember. Pendekatan penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian fenomenologis. Metode pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Analisis data menggunakan model analisis interaktif Miles dan Huberman, dengan proses data collection, condensation, data display, and data verifiying. Untuk menguji keabsahan data menggunakan trianggulasi. Hasil penelitian ini menunjukkan bahwa: 1) Pada tahap presentasi, guru memulai dengan materi cerita, mereview ulang materi sebelumnya, dan kegiatan belajar dalam tim. 2) Guru menyiapkan lembaran kerja sebagai pedoman kerja kelompok dan setiap anggota dapat berkontribusi, guru melakukan pengamatan, memberikan bimbingan, motivasi, dan bantuan jika diperlukan. 3) Tes individu dalam kelompok. 4) Skor pengembangan bagi individu, guru menggabungkan skor nilai sebelumnya dengan skor akhir. 5) Penghargaan bagi tim mendasarkan kepada penilaian terhadap individu dalam kelompok sehingga proses rekapitulasi penilaian kelompok, didasarkan kepada penilain individu masing-masing kelompok. Kata Kunci: Model STAD; Pembelajaran, Tematik; Sekolah Dasar